KOSMOSENTRISME TAFSIR QS. AS-SYAMS AYAT 1-6: PENERAPAN TAFSIR ILMI DALAM TELAAH ILMU FALAK - SYUKUR (ELFALAKY: Jurnal Ilmu Falak, 2022)
The contents of the Qur'an are full of cosmocentrism dimensions that elaborate on various phenomena of the universe in it. Normative theological cues that Allah swt. convey to QS. as-Shams verses 1-6 is one of the illustrations of the Qur'an that directs humans to understand themselves by referring to various phenomena of the universe because reading the universe is an inseparable part of reading the verses of Kauniyah in addition to reading the verses qauliyah written in the Qur'an so that scientific interpretation becomes one of the appropriate interpretation approaches in its interpretation. Humans are creatures who have been equipped with various potentials, both empirical senses and rational reason, so that they are always directed to observe and reason a lot about cosmocentric universe phenomena. QS. as-Shams verses 1-6 describe how the sun, moon, day, night, sky, and earth with all the sunnatullah framework that accompanies it become one of the objects of study of astronomy which has many epistemological intersections with various cosmocentric universe phenomena through scientific interpretation.